Potential Therapeutic Efficacy of Ferulic Acid and Its Derivatives in the Management of Cancers: A Comprehensive Analysis With Mechanistic Insight - Shakil Ahmmed; Md. Shimul Bhuia; Raihan Chowdhury; Md. Hanif Munshi; Tanzila Akter Eity; Hossam Kamli; Muhammad Torequl Islam (International Journal of Food Science)
Due to the increasing rate of cancer and the undesirable consequences of manufactured drugs, there is a growing interest in the development of natural products as potential remedies. Ferulic acid (FA), a phenolic substance, is found naturally present in the Ferula foetida plant’s cell walls with therapeutic activities. The objective of this study is to determine the botanical sources, pharmacokinetics, and anticancer activity of FA and its derivatives, focusing on the molecular mechanism by using the data obtained from the literature database. The study’s findings suggest that FA demonstrates promising anticancer effects in preclinical pharmacological test methods. The findings of the study exhibit that FA showed promising anticancer activity through underlying mechanisms, including induction of oxidative stress, cytotoxic effect, cell cycle arrest, apoptotic effect, suppression of invasion and migration, antiproliferative effect, autophagy, and genotoxic and mutagenic effect by regulating different molecular pathways like PI3K/AKT, p38/MAPK/ERK, AKT/mTOR, and NF-κB signaling pathways which are involved in cancer development and cell growth. Additionally, this review indicated the pharmacokinetic properties of FA, indicating lower oral bioavailability is affected by the liver’s fast conjugation process; this limitation is overcome by applying a nanoformulation of FA. However, additional clinical investigations are recommended to determine the appropriate therapeutic effectiveness, safety, and human dosage.